Cooling and performance recovery of trained athletes: a meta-analytical review - Poppendieck, W.; Faude, O.; Wegmann, M.; Meyer , T. (International Journal of Sports Physiology and Performance, 2013)
Purpose: Cooling after exercise has been investigated as a method to improve recovery during intensive training or competition periods. As many studies have included untrained subjects, the transfer of those results to trained athletes is questionable. Methods: Therefore, the authors conducted a literature search and located 21 peer-reviewed randomized controlled trials addressing the effects of cooling on performance recovery in trained athletes. Results: For all studies, the effect of cooling on performance was determined and effect sizes (Hedges` g) were calculated. Regarding performance measurement, the largest average effect size was found for sprint performance (2.6%, g = 0.69), while for endurance parameters (2.6%, g = 0.19), jump (3.0%, g = 0.15), and strength (1.8%, g = 0.10), effect sizes were smaller. The effects were most pronounced when performance was evaluated 96 h after exercise (4.3%, g = 1.03). Regarding the exercise used to induce fatigue, effects after endurance training (2.4%, g = 0.35) were larger than after strength-based exercise (2.4%, g = 0.11). Cold-water immersion (2.9%, g = 0.34) and cryogenic chambers (3.8%, g = 0.25) seem to be more beneficial with respect to performance than cooling packs (-1.4%, g = -0.07). For cold-water application, whole-body immersion (5.1%, g = 0.62) was significantly more effective than immersing only the legs or arms (1.1%, g = 0.10). Conclusions: In summary, the average effects of cooling on recovery of trained athletes were rather small (2.4%, g = 0.28). However, under appropriate conditions (whole-body cooling, recovery from sprint exercise), postexercise cooling seems to have positive effects that are large enough to be relevant for competitive athletes.